Interaction between labour law and immigration regimes: The case of short-term third-country national workers in the EU and the EEA - Zane Rasnača; Vladimir Bogoeski (European Trade Union Institute (ETUI), 2023)
This report provides an overview of the ways in which EU and EEA Member States regulate the immigration of third-country nationals who enter their territory for the purpose of work. Its focus is on short-term migrant workers and it presents the result of an extensive mapping exercise carried out by national experts from 23 EU and two EEA countries in collaboration with the ETUI. It focussed on the interaction between immigration law regimes and labour market access, as well as the employment rights of different categories of short-term third-country national workers, depending on their immigration status. While every third-country national worker in the EU should, in principle, be treated with respect, dignity and on a non-discriminatory basis in comparison with local workers, it is clear that that is not always the case (Strauss and McGrath 2017; Leboeuf 2021; van Ginneken 2013). In comparison with local workers, thirdcountry nationals are particularly vulnerable because of the often existing link between their immigration status and their labour market access (Mantouvalou 2020). The present report aims to expose how different countries have dealt with this vulnerability in the context of concrete categories of workers. It thus explores the immigration pathways available to third-country national workers and provides an overview of the conditions for entry, stay and leave for each national system for short-term workers, depending on category. Special attention is paid to posted workers from third countries, as well as whether temporary agency work is permitted for third-country nationals in various EU and EEA countries, and its modalities. Finally, we also provide a short overview of the Covid-19 pandemic's impact on third-country national workers and the specific features of national systems dedicated to the enforcement of their rights.
Keywords: 330; Internationale Migration; Einwanderung; Arbeitsmigranten; Migrationspolitik; Arbeitsmarktintegration; Arbeitsrecht; EWR-Staaten; EU-Staaten